2017
DOI: 10.1080/00223891.2016.1269775
|View full text |Cite
|
Sign up to set email alerts
|

Personality Assessment Inventory Scores as Predictors of Evaluation Referrals, Evaluator Opinions, and Commitment Decisions in Sexually Violent Predator Cases

Abstract: We used data from more than 1,500 offenders to examine the association between Personality Assessment Inventory (PAI; Morey, 1991 ) scores and progress through the sexually violent predator (SVP) screening, evaluation, and commitment process. There was no clear association between PAI scores and referrals for full evaluations, but PAI scores were small to moderate predictors of evaluator opinions and diagnoses among offenders who underwent full evaluations. Higher Antisocial Features (ANT) scores were associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Such response behaviors, particularly among a sample of male sexual offenders against children, suggest that this type of offender may be overtly managing others' impressions of them (Tarascavage et al 2018). What is more, minimizing symptoms and behaviors through defensive response styles has been indicated as a predictor of sexual offenders receiving diagnoses of Antisocial Personality Disorder (Boccaccini et al 2017). These findings are important given that antisocial traits and personality characteristics are predictive of both general and sexual recidivism (Hanson and Morton-Bourgon 2005).…”
Section: Legal Considerationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Such response behaviors, particularly among a sample of male sexual offenders against children, suggest that this type of offender may be overtly managing others' impressions of them (Tarascavage et al 2018). What is more, minimizing symptoms and behaviors through defensive response styles has been indicated as a predictor of sexual offenders receiving diagnoses of Antisocial Personality Disorder (Boccaccini et al 2017). These findings are important given that antisocial traits and personality characteristics are predictive of both general and sexual recidivism (Hanson and Morton-Bourgon 2005).…”
Section: Legal Considerationsmentioning
confidence: 98%
“…Another form of evaluation that is likely to be useful and relatively more cost-effective compared with imaging studies, is personality assessment. Research examining personality characteristics of sexual offenders have found that sexual offenders may respond differently during assessment and some characteristics are more likely to be related to certain offender types and to reoffending (Boccaccini et al 2017;Tarascavage et al 2018).…”
Section: Legal Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…O PAI tem revelado utilidade em contextos forenses (e.g., correcional, prisional, pericial), auxiliando, a título de exemplo, na avaliação do risco de reincidência criminal e de infrações disciplinares de reclusos (e.g., Boccaccini et al, 2010;Gardner et al, 2015;Jung et al, 2018;Reidy et al, 2016;Ruiz et al, 2014), na avaliação do risco de violência (e.g., Boccaccini et al, 2017;Humenik et al, 2019;Reidy et al, 2016), na avaliação de simulação de sintomas (e.g., Boccaccini et al, 2006;Edens et al, 2007;Kucharski et al, 2007) e na avaliação da competência para ir a tribunal (e.g., Edens et al, 2001;Lally, 2003;Mullen & Edens, 2008).…”
Section: Contexto Forenseunclassified